Nontuberculous Mycobacterial Osteomyelitis of the Thumb: Successful Treatment with Serial Debridement, Antimicrobial Therapy, External Fixation, and Interphalangeal Arthrodesis: A Case Report. Issue 4 (14th October 2015) - Ehrlichman, Lauren K.; Kadzielski, John J.; Hyle, Emily P.; Jupiter, Jesse B.
Abstract : Case: : We present the case of a fifty‐seven‐year‐old woman treated for persistent inflammation of her thumb initially thought to be due to tuberculous osteomyelitis but which ultimately proved to be due to infection caused by a novel nontuberculous mycobacterial species. The establishment of this diagnosis and her treatment are described. Conclusion: : Indolent hand infections caused by atypical mycobacterial species may occur even in immunocompetent hosts, and their diagnosis remains challenging and often elusive. Surgeons should have a low threshold of suspicion for nontuberculous mycobacteria in cases refractory to treatment by standard protocols. The miniature external fixator provides stability and allows for soft‐tissue healing in the setting of hand infections.